Climatological Characteristics of the Monsoon Breaks during the Southwest Monsoon Season of the Philippines - Olaguera, Lyndon Mark P. (Archīum Ateneo, 2023)
This study investigates the climatological characteristics of the monsoon breaks during the southwest monsoon season (June–September) of the Philippines from 1979 to 2020. The monsoon break is defined as a period when the average rainfall across the eight western coast stations of the Philippines decreases below 5 mm·day−1 for at least three consecutive days. About 208 monsoon break events were identified, with 131 short- (3–4 days; 63% of the total monsoon break events), 71 medium- (5–9 days; 34%) and 6 long-duration (≥10 days; 3%) monsoon break events. The short- and medium-duration monsoon breaks were found to be more frequent during June and less frequent during August. Lag composite analyses of the time series of rainfall, low level zonal wind (UWND850hPa), vertically integrated moisture flux convergence (VIMFC) and mid-tropospheric geopotential height (HGT500hPa) relative to the starting date of the monsoon break events show that the monsoon break is characterized by decrease in rainfall, weakening of westerly winds, increase in HGT500hPa and suppression of VIMFC over Luzon Island. Further analyses of the large-scale circulation features show the appearance of an anticyclonic circulation over Luzon Island that suppresses the rainfall in the region and westward extension of the western North Pacific Subtropical High (WNPSH). The occurrence of the monsoon break events appears to be modulated by the 30–60-day mode of the boreal summer intraseasonal oscillation (BSISO). About 39%, 55% and 82% of the short-, medium- and long-duration monsoon break events occur between Phases 1 and 4 during significant suppressed phases of the BSISO (i.e., amplitude >1), respectively. Convective activities and tropical cyclone activities are generally suppressed in these phases. The suppression of convective activities near the Philippines may facilitate the westward expansion of WNPSH, which further suppresses the rainfall and weaken the southwest monsoon.